1985
DOI: 10.1093/ije/14.4.555
|View full text |Cite
|
Sign up to set email alerts
|

Are Maternal Fertility Problems Related to Childhood Leukaemia?

Abstract: An explorative case-control study was conducted in The Netherlands. The cases were obtained from a complete nationwide register of childhood leukaemia (1973-1980). Controls were matched with the cases for year of birth, sex and place of residence. Information about exposures of the mother to potential risk factors in the year before pregnancy and during pregnancy was collected via mailed questionnaires. The analyses concerned data on 519 patients with acute lymphocytic leukaemia and 507 controls. An associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
64
4
6

Year Published

1988
1988
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(84 citation statements)
references
References 0 publications
10
64
4
6
Order By: Relevance
“…Earlier studies had observed a leukaemia risk for first-born children (McMahon and Newill, 1962;Stark and Mantel, 1966;Van Steensel-Moll et al, 1986). In agreement with other investigations, the duration of breastfeeding was not significantly associated with leukaemia risk (Hartley et al, 1988;Van Duijn et al, 1988;Shu et al, 1995;Petridou et al, 1997).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Earlier studies had observed a leukaemia risk for first-born children (McMahon and Newill, 1962;Stark and Mantel, 1966;Van Steensel-Moll et al, 1986). In agreement with other investigations, the duration of breastfeeding was not significantly associated with leukaemia risk (Hartley et al, 1988;Van Duijn et al, 1988;Shu et al, 1995;Petridou et al, 1997).…”
Section: Discussionsupporting
confidence: 85%
“…Distinguishing between the infections, we found a risk reduction for chickenpox for all leukaemias and an elevated risk for pneunomia for common-ALL. A negative association between infections in the first year of life and childhood leukaemia was reported by Van Steensel-Moll et al (1986). We could not confirm this observation in our studies.…”
Section: Discussioncontrasting
confidence: 79%
“…Most previous reports failed to find an association between ALL and length of gestation (Kaye et al, 1991;Kaatsch et al, 1996;McKinney et al, 1999), although one study has shown a similar, but not statistically significant, relationship (Dockerty et al, 1999). Some studies have reported positive associations between history of previous foetal loss and childhood leukaemia (van Steensel-Moll et al, 1985;Kaye et al, 1991), others found no association (Schuz et al, 1999) while in the current study, as in a Chinese case -control study (Shu et al, 1988) an inverse association was found. Possible mechanisms for a positive association include environmental exposures and genetic predisposition but the issues of selective participation and recall bias have not been fully addressed.…”
Section: Gestational Age and Previous History Of Miscarriagecontrasting
confidence: 50%
“…Recently there has been growing interest in the relationship between prenatal and early life influences on risk of childhood leukaemia (Van Steensel-Moll et al, 1985;Shu et al, 1988;Kaye et al, 1991;Westergaard et al, 1997;McKinney et al, 1999). It is clear that mutations occurring in-utero in lymphoid stem cells contribute to the development of childhood leukaemia (Greaves, 1999;Wiemels et al, 1999) but it is not known which prenatal exposures result in these mutations or how they may be prevented.…”
mentioning
confidence: 99%
“…A few earlier studies published in the 1960s or early 1970s suggested a weak increased risk of leukaemia or leukaemia death among offspring born to older mothers in the United States (Manning and Carroll, 1957;MacMahon and Newill, 1962;Stark and Mantel, 1969;Fasal et al, 1971). Since then, however, most studies of maternal age and the risk of leukaemia in the offspring have been negative or have shown weak, nonsignificant elevated risk with older maternal age (Salonen and Saxen, 1975;Kneale and Stewart, 1976;Shaw et al, 1984;Steensel-Moll et al, 1985;McKinney et al, 1987McKinney et al, , 1999Shu et al, 1988Shu et al, , 1994Shu et al, , 1999Zack et al, 1991;Cnattingius et al, 1995;Petridou et al, 1997;Roman et al, 1997;Ross et al, 1997;Westergaard et al, 1997;Dockerty et al, 1999;Thompson et al, 2001;Murray et al, 2002;Okcu et al, 2002;Jourdan-Da Silva et al, 2004). A handful of studies have resulted in statistically significant increased risk ratios in the order of 1.5 -2.0 for ALL or all leukaemias among children born to women older than age 35 years at delivery (Kaye et al, 1991;Buckley et al, 1994;Hemminki et al, 1999;Mogren et al, 1999;Dockerty et al, 2001;Reynolds et al, 2002;Shu et al, 2002;Jourdan-Da Silva et al, 2004).…”
Section: Discussionmentioning
confidence: 99%